2022
DOI: 10.3390/pharmaceutics14020322
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Antitumor Effect of Photodynamic Therapy and Chemotherapy Mediated by Nano Drug Delivery Systems

Abstract: This review provides a summary of recent progress in the development of different nano-platforms for the efficient synergistic effect between photodynamic therapy and chemotherapy. In particular, this review focuses on various methods in which photosensitizers and chemotherapeutic agents are co-delivered to the targeted tumor site. In many cases, the photosensitizers act as drug carriers, but this review, also covers different types of appropriate nanocarriers that aid in the delivery of photosensitizers to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 271 publications
(326 reference statements)
0
16
0
Order By: Relevance
“…With their unique 2D layered structure and high physical and chemical properties, including hydrophilicity, biocompatibility, light-heat conversion performance and mechanical flexibility [ 27 ], MXenes can be used in a variety of biomedical applications, including sensors [ 78 ], bioimaging [ 79 ], tissue engineering [ 10 ], photothermal therapy [ 80 ], antibacterial photothermal therapy [ 81 ], antibacterial therapy and drug delivery systems [ 10 , 82 ], among others.…”
Section: Biomedical Applications Of Mxenesmentioning
confidence: 99%
See 1 more Smart Citation
“…With their unique 2D layered structure and high physical and chemical properties, including hydrophilicity, biocompatibility, light-heat conversion performance and mechanical flexibility [ 27 ], MXenes can be used in a variety of biomedical applications, including sensors [ 78 ], bioimaging [ 79 ], tissue engineering [ 10 ], photothermal therapy [ 80 ], antibacterial photothermal therapy [ 81 ], antibacterial therapy and drug delivery systems [ 10 , 82 ], among others.…”
Section: Biomedical Applications Of Mxenesmentioning
confidence: 99%
“…Ti 3 C 2 -based nanoplatforms for synergistic PTT, PDT and chemotherapy were developed by Liu et al [ 80 , 81 ]. When irradiated with an 808 nm laser, the produced Ti 3 C 2 -based nanosheets showed an excellent extinction coefficient value of 28.6 Lg −1 ·cm −1 , an amazing efficiency for photothermal conversion of around 58.3% and effective creation of singlet oxygen [ 81 ]. Doxorubicin (DOX), a chemotherapeutic drug, was placed in MXene with a hyaluronic acid coating applied to its surface (HA) to boost its biocompatibility.…”
Section: Biomedical Applications Of Mxenesmentioning
confidence: 99%
“…Nonetheless, they showed that the conjugate produced an enhance 1 O 2 quantum yield compared with free PS with regards to fluorescence. Liu et al [ 76 , 77 ] conjugated a NIR PS to AgNP/carbon dot nanohybrids and found that the conjugate induced great levels of 1 O 2 and enhanced cell death in vivo in xenograft mouse models of breast cancer, compared with free PS or the nanohybrids alone. While several researchers have shown the photodynamic effect of AgNPs as PSs and the synergetic effects of this combined chemotherapy [ 77 ], there is little literature on the use of PS-loaded AgNPs being used in PDT.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…armaceutics 2022, 14, 1375 2 of 16 subcellular structures, such as cell membrane and organelle membrane, by the rapid oxidation of biomolecules, in a localized manner [5][6][7], as ROS are extremely active with a short diffusion radio. More importantly, cancer phototherapy showed a synergistic effect with other cancer therapies by promoting a cargo release upon laser irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Such temperature elevation-induced cell inhibition can be dramatically intensified due to the insufficient circulating system inside tumor tissues. For PDT, the light irradiation-generated ROS can destroy subcellular structures, such as cell membrane and organelle membrane, by the rapid oxidation of biomolecules, in a localized manner [ 5 , 6 , 7 ], as ROS are extremely active with a short diffusion radio. More importantly, cancer phototherapy showed a synergistic effect with other cancer therapies by promoting a cargo release upon laser irradiation.…”
Section: Introductionmentioning
confidence: 99%